Evapotranspiration-Based Irrigation Management Effects on Yield and Water Productivity of Summer Cauliflower on the California Central Coast - Michael Cahn; Lee Johnson; Sharon Benzen (Horticulturae)
Improvements in irrigation water productivity constitute an ongoing effort globally. In California, growers are under regulatory pressure to stabilize groundwater levels and reduce nitrate leaching, partially, by further improvements in irrigation optimization. Evapotranspiration (ET)-based methods can inform crop water requirements and boost irrigation efficiency, but in practice, they can be challenging for farmers to implement, especially in vegetable systems. Irrigation field trials were conducted near Salinas CA in 2018 and 2019 to evaluate the crop coefficient model employed by the CropManage ET-based irrigation decision support system (DSS) for summer cauliflower (Brassica oleracea var. botrytis cv. Symphony) and investigate potential water savings through improved irrigation scheduling. Overhead sprinklers were used for crop establishment, and surface drip was used subsequently. A randomized complete block design was used to administer treatments near 50, 75, 100, and 150% of crop evapotranspiration (ET) during the drip period with an added treatment at 125% in 2019. Water requirement for the 100% treatment was determined by the CropManage DSS model based on crop coefficients derived from fractional canopy cover. Deliveries to remaining treatments were scaled proportionally. The total yield and irrigation productivity were maximized by the 100% treatment both years with total applied water ranging from 275 to 300 mm. At present, the reported water application for summer cauliflower averages 465 mm in the region. Hence, implementing ET-based irrigation scheduling, administered through the CropManage DSS, could reduce water use in summer cauliflower by an average of 30% relative to current practices and serve to enhance groundwater management while maintaining crop returns.